Delay in Diagnosis of Autoimmune Polyendocrine Syndrome Type 2 as a Consequence of Misinterpretation of Gastrointestinal Symptoms - Maciej Gonciarz; Michał Krogulecki; Dorota Brodowska-Kania; Szczepan Cierniak; Grzegorz Kamiński (Case Reports in Gastrointestinal Medicine)
Background. Type 2 autoimmune polyendocrine syndrome (APS-2) is characterized by the presence of at least two of three endocrinopathies: Addison’s disease, autoimmune thyroiditis, and diabetes type 1. The prevalence of APS-2 is estimated to be 1 : 1000 to 1 : 20.000 in the general population. Diagnosis of APS-2 often is delayed due to its rarity and wide spectrum of clinical symptoms. Case Presentation. A 27-year-old presented with a 6-month history of abdominal pain, vomiting, diarrhea, weakness, fatigue, and 15 kg of weight loss. The patient was diagnosed with Crohn’s disease in a local hospital and referred to our institution because of treatment failure. Colonoscopy performed in this hospital identified irregular mucosal erosions in terminal ileum, and the microscopy of biopsy specimens demonstrated nonspecific inflammation. On physical examination, the patient appeared cachectic. Blood pressure was 90/60 mmHg. Laboratory results were significant for severe hyponatremia and mild hyperkalemia. Morning cortisol was low, and adrenocorticotropic hormone (ACTH) concentration was high. An ACTH stimulation test did not present any increase in serum cortisol, which confirmed primary adrenal insufficiency. Antithyroid peroxidase antibody (anti-TPO) as well as both anti-21-hydroxylase antibodies and antiglutamic acid decarboxylase antibodies (GAD65) were positive. So, the diagnosis of APS-2 was made, and the replacement doses of hydrocortisone and fludrocortisone has brought a rapid improvement in all clinical symptoms; colonoscopy showed normal. Conclusion. The case presented herein highlights rapidly progressive nature of untreated APS-2 and that the diagnosis of APS-2 may be challenging.